Symptomatic relief through Ayurveda treatment in the patient of interstitial lung disease - Palak Sanjeev Singhal; Ruchi Purohit; Pankaj Chhayani; Manish V Patel (Journal of Ayurveda, 2023)
Introduction: Interstitial lung diseases (ILDs) are nonmalignant and noninfectious chronic conditions characterized by dyspnea and cough. Main Clinical Finding: A patient of 32 years had shortness of breath at rest and was aggravated by walking or exertion, coughing for the past 2 years, and decreased appetite for 10 years. Diagnosis: The patient visited physician in his hometown, who after conducting various diagnostic imaging referred him to a chest physician, where he diagnosed ILD (cystic lung disease). Interventions: The patient was hospitalized and treated with Ayurveda treatment, i.e., snehapana, virechana, and sanshamana chikitsa for 3 weeks. After that, the patient was instructed to continue oral medicaments, i.e., sanshamana chikitsa at home and is continuing the same to date and further relief was also noted. Outcome: After the hospitalization period, the patient did not require any conventional care medicine. The patient had visible relief within a few days of starting the treatment and was able to walk long distances without complaining of any shortness of breath. Conclusions: The collected data from this study suggest that Ayurveda treatment can provide noteworthy relief in ILD and further research will be helpful.